Innovative Transformation Through Biblical Counseling in Serving the Spiritual Community - Herman, Samuel; Hindradjat, Juliana (International Journal of Multicultural Counseling and Development, 2024)
Counseling services in the local church play a significant role in creating positive transformation. Pastors guide the congregation in overcoming issues, crises, and behaviors inconsistent with the teachings of the Bible. The success of counseling depends not only on counselor-client collaboration but also on understanding principles and using appropriate tools. The counseling process involves support, guidance, and direction with the help of the Holy Spirit and biblical teachings. Prayer is crucial for victory and faith growth during crises. Maintaining confidentiality and reliable methods is vital for counselors. Christian counseling leverages unique access to two sources: the Holy Spirit's wisdom and the Bible's guidance in the counseling process.